FUNCTIONAL TYPES OF INTERROGATIVE SENTENCES: A LINGUISTIC AND PRAGMATIC ANALYSIS - SAIDOVA, Mamura Suleymanovna (The Lingua Spectrum, 2025)
Interrogative sentences are central to human communication, enabling speakers to request information, confirm assumptions, and negotiate meaning. This paper examines the functional types of interrogative sentences in English – yes/no questions, wh-questions, alternative questions, tag questions, and indirect questions – through a linguistic and pragmatic lens. Using descriptive and contextual analysis, the study highlights their syntactic structures, communicative roles, and discourse functions. Findings suggest that interrogatives extend beyond mere information-seeking, serving pragmatic functions such as politeness, persuasion, and rhetorical effect.